1980
DOI: 10.1017/s0021859600088018
|View full text |Cite
|
Sign up to set email alerts
|

Protection of leaf protein of lucerne (Medicago sativa L.) against degradation in the rumen by treatment with formaldehyde and glutaraldehyde

Abstract: SUMMARYAqueous glutaraldehyde, in the presence of wetting agents Tween-20 or Haemosol, reacted with fresh cut lucerne (Medicago sativa L.), complete reaction being obtained with about 7·2 g (72 mmol)/kg herbage, or 18g/100g crude protein. Reaction with 25% w/v aqueous glutaraldehyde sprayed on to fresh lucerne was rapid, and at the rate of 66 mmol/kg lucerne, all aldehyde had reacted in 3 h and about 60% of the soluble leaf protein became insoluble. Formaldehyde at twice the molar concentration of glutaraldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Both formaldehyde and glutaraldehyde possess antimicrobial properties which, whilst of potential benefit during ensiling, could be harmful in the rumen. Mangan et al (1980) observed reduced microbial motility in the rumen when cattle were given formaldehydetreated lucerne but not when they were given glutaraldehyde-treated lucerne. An adverse effect of formaldehyde-treated silage on rumen microbes, as evidenced by a decreased microbial N flow at the duodenum, was also found in the study of Beever et al (1977), although this did not occur in other studies (Siddons et al 1979;Thomson et al 1981;Overend & Armstrong, 1982).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Both formaldehyde and glutaraldehyde possess antimicrobial properties which, whilst of potential benefit during ensiling, could be harmful in the rumen. Mangan et al (1980) observed reduced microbial motility in the rumen when cattle were given formaldehydetreated lucerne but not when they were given glutaraldehyde-treated lucerne. An adverse effect of formaldehyde-treated silage on rumen microbes, as evidenced by a decreased microbial N flow at the duodenum, was also found in the study of Beever et al (1977), although this did not occur in other studies (Siddons et al 1979;Thomson et al 1981;Overend & Armstrong, 1982).…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, soluble protein content did decrease between additive application and completion of ensiling but this was probably due to precipitation by formic acid since it occurred to a similar extent with all treatments and was not accompanied by an increase in NPN content. The presence of formic acid in all additives may also explain the absence of a more rapid reaction between glutaraldehyde and protein than between formaldehyde and protein, as observed by Mangan et al (1980), because aldehyde-protein bonds are less stable at low pH (Ferguson et al 1967).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Medicago sativa L) (McArthur & Miltimore, 1961). During mastication of herbage by cattle, fraction I is readily released from plant tissues and is freely available to the rumen microflora in large amounts (Mangan et al 1976). Preliminary communications of some of the results have been given (Nugent & Mangan, 1978;Nugent, 1978).…”
mentioning
confidence: 99%